Class Management in Growing Early Children's Religious Development - Reza Saeful Rachman; Pandu Adi Cakranegara; Syafrudin Syafrudin; Abdul Hafiz; Hadisa Putri (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This study aimed to analyze classroom management's implications on the spiritual development of early childhood. The method used in this research is the library research method. Research analysis by collecting data from previous research and managing all information and theories relevant to the research study from several sources such as books and journals. The result of this study is that classroom management gives teachers sufficient time to build classroom management practices, some with intensive coaching and feedback. It is essential because coaching can increase classroom management's efficacy, which is linked to the child's growth, and the proper guidance in school leads to moral and academic excellence. Well managed in the classroom, it creates space for positive student behavior, academic excellence, and the formation of a religious character.